2016
DOI: 10.1016/j.mito.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Pif1 helicase causes a mitochondrial myopathy in mice

Abstract: Mutations in genes coding for mitochondrial helicases such as TWINKLE and DNA2 are involved in mitochondrial myopathies with mtDNA instability in both human and mouse. We show that inactivation of Pif1, a third member of the mitochondrial helicase family, causes a similar phenotype in mouse. pif1−/− animals develop a mitochondrial myopathy with respiratory chain deficiency. Pif1 inactivation is responsible for a deficiency to repair oxidative stress-induced mtDNA damage in mouse embryonic fibroblasts that is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…Despite the presence of mtDNA deletions, Deletor mice do not display decreased physical performance or increased body weight [35]. These results from the Deletor mice suggest that the mtDNA deletions in the skeletal muscle of PIF1 KO mice previously described [4] do not contribute to the decreased activity and increased body weight shown in the current study.…”
Section: The Dissociation Between Obesity and Metabolic Dysfunction Isupporting
confidence: 59%
See 1 more Smart Citation
“…Despite the presence of mtDNA deletions, Deletor mice do not display decreased physical performance or increased body weight [35]. These results from the Deletor mice suggest that the mtDNA deletions in the skeletal muscle of PIF1 KO mice previously described [4] do not contribute to the decreased activity and increased body weight shown in the current study.…”
Section: The Dissociation Between Obesity and Metabolic Dysfunction Isupporting
confidence: 59%
“…Wild type C57BL/6J mice were from the Jackson Laboratory (Bar Harbor, ME). PIF1 KO mice were originally developed in the C57BL/6 background [4,12], but the Pif1 deletion was maintained in the C57BL/6J background exclusively for more than 10 generations. Animals were fed normal or WD chow ad libitum and housed in a 12 h light to dark cycling room.…”
Section: Animalsmentioning
confidence: 99%
“…Recent studies have shown Twinkle helicase to be essential for mtDNA replication, as depletion of Twinkle causes severe mtDNA depletion (10). Pif1 is another helicase that has also been shown to cause mitochondrial instability: depletion of Pif1 causes deficiency in repairing oxidative stress-induced mtDNA damage and mitochondrial myopathy (11). POLG is crucial as it is the only replicative, highly-processive polymerase in the mitochondria, and also is necessary in the repair of mtDNA (12).…”
Section: Mtdna In Mitochondrial Bioenergetics and Biogenesismentioning
confidence: 99%
“…Mice lacking PIF1 show a mitochondrial myopathy, suggesting a subtle role in mtDNA maintenance (BANNWARTH et al 2016). The expression of mouse and human PIF1 is limited to highly proliferating embryonic stem cells and peaks in late S/G2 phase, consistent with a role in DNA replication (MATEYAK AND ZAKIAN 2006).…”
Section: Introductionmentioning
confidence: 95%